Relationship Between Serum Magnesium and Parathyroid Hormone Levels in Hemodialysis Patients - Abdulaziz, Lorans Mohamad; Saied, Hussein; Redwan, Faisal (Journal of medical and pharmaceutical sciences, 2022)
Objective: The aim of this study is to investigate the relationship between serum magnesium and parathyroid hormone levels in hemodialysis patients. In addition to, study the prevalence of parathyroid disorders among hemodialysis patients.Methods: it is (Cross- Sectional) Study conducted for the period of one year (May 2019 –May 2020) at Tishreen University Hospital in Lattakia- Syria. The study included 82 patients with chronic kidney disease (CKD) undergoing hemodialysis, Laboratory analysis of calcium; phosphorous, magnesium and parathyroid hormone were conducted for all patients before starting the dialysis session. The values ​​of PTH were compared according to the serum magnesium, we also studied the prevalence of parathyroid disorders among hemodialysis patients.Results: The mean age was (51.62 years), and the mean duration of dialysis was (4.09 years), and (60% males, 40% females). We found in all patients normal or high serum magnesium, (36.58 % normal, 63, 42 % high), the mean of magnesium (2.78 mg/dl), and the mean of PTH (295 Pg/ml), mean of calcium (8.64 mg/dl), mean of phosporous (5.6 mg/dl). we found statistically significant differences in PTH ​​between the group of patients with normal magnesium and the group with hypermagnesium (Mg>2.5 mg/dl), where the mean PTH values ​​were (339.4 ± 68 pg/ml) in the normal magnesium group, and the mean PTH was (272.3 ± 43 pg/ml) in the hypermagnesium group (P.value=0.01).We found a negative linear correlation between magnesium and PTH (r=- 0.311, p=0.03), We also found that the values ​​of PTH were outside the acceptable range (2- 9 times the upper normal limit) in (24.4%)of patients.Conclusions: There is a statistically significant inverse relationship between serum magnesium and PTH, and this relationship is independent of calcium and phosphorous.
Keywords: chronic kidney disease; magnesium; PTH; Hemodialysis